IncreasMeningkatkan Kompetensi Guru dalam Mendukung Tantangan Keberlanjutan Pengajaran di Era Globaling Teacher Competency in Supporting Teaching Sustainability Challenges in the Global Era - Kusnandi Kusnandi (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah kendari, 2024)
This research aims to explore the role of teacher competence in addressing the challenges of sustainable learning in the era of globalization. The method used is a qualitative approach with a literature review, involving the identification, collection, and analysis of relevant literature from Google Scholar between 2015 and 2023, using the keyword